Pembekalan Sistem Penjurnalan Perusahaan Dagang untuk Siswa Siswi SMA Kristoforus - Dewi, Sofia Prima; Setiawan, Levina; Tan, Michelle (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2025)
There are three types of businesses in Indonesia based on their activities: service, trading, and manufacturing. The operational characteristics of these three types of businesses are not the same. In accounting for all types of businesses, journals are the first accounting record. Journals play a crucial role because they significantly influence financial statements, the final product of accounting. Mistakes in journal entries will result in errors in the preparation of financial statements and will certainly mislead users of financial statements in decision-making. Younger generations, such as students, need an understanding of accounting journals, especially journals for trading companies, to face future challenges. The problem faced by partners is that many students are interested in accounting topics but have limited time in class, making it impossible to practice questions in depth. The solution to this problem is for Kristoforus High School, in collaboration with the UNTAR PKM team, to provide training on journaling systems for trading companies. The PKM activity method is divided into several stages. First, developing a module on journaling systems for trading companies. Second, providing general concepts regarding journaling systems for trading companies. Third, the program provides specific conceptual guidance on journaling systems for trading companies, along with sample questions. The final stage involves independently completing practice questions and quizzes. The PKM activity, conducted offline on September 23, 2025, at Kristoforus High School, proved effective in addressing partner issues. This was evident in the students' enthusiasm and satisfactory quiz results.